2008
DOI: 10.1007/s00425-008-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of callose synthase genes and its connection with Npr1 signaling pathway during pathogen infection

Abstract: Callose synthesis occurs at specific stages of plant cell wall development in all cell types, and in response to pathogen attack, wounding and physiological stresses. We determined the expression pattern of "upstream regulatory sequence" of 12 Arabidopsis callose synthase genes (CalS1-12) genes and demonstrated that different callose synthases are expressed specifically in different tissues during plant development. That multiple CalS genes are expressed in the same cell type suggests the possibility that CalS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 53 publications
4
119
0
Order By: Relevance
“…Further studies will be needed to determine whether RLCK281 is involved in regulating SA signaling. Additionally, studies on phytohormone defense signaling have shown that SA treatment can affect callose synthase gene expression (Jacobs et al, 2003;Dong et al, 2008). We propose that LOC_Os01g67364.1 may function as part of a callose synthase and contribute to callose accumulation to protect plants against BPH attack.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 91%
“…Further studies will be needed to determine whether RLCK281 is involved in regulating SA signaling. Additionally, studies on phytohormone defense signaling have shown that SA treatment can affect callose synthase gene expression (Jacobs et al, 2003;Dong et al, 2008). We propose that LOC_Os01g67364.1 may function as part of a callose synthase and contribute to callose accumulation to protect plants against BPH attack.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 91%
“…In Arabidopsis thaliana, 12 callose synthase genes are described [4]. They showed a tissue-specific expression [6], which was also reported from callose synthase genes in wheat [7]. Among the 12 callose synthases in A. thaliana, PMR4 (POWDERY MILDEW RESITANT 4, also called GLU-CAN SYNTHASE LIKE 5) is responsible for woundand pathogen-induced callose formation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Callose is synthesized from the sugar nucleotide UDPglucose via callose synthases that span the plasma membrane. In both vascular and nonvascular plants, callose synthases are encoded by multigene families, and different isoforms have different locations and functions in the plant (Voigt et al, 2006;Dong et al, 2008;Schober et al, 2009;Schuette et al, 2009). Of the 12 Glucan Synthase-Like (GSL; also called CalS) genes in Arabidopsis (Arabidopsis thaliana), five are suggested or proven from mutational and correlative analyses to encode isoforms with important functions in pollen development (GSL1, GSL2, GSL5, GSL8, and GSL10; Enns et al, 2005;Nishikawa et al, 2005;Tö ller et al, 2008;Huang et al, 2009).…”
mentioning
confidence: 99%
“…Of the 12 Glucan Synthase-Like (GSL; also called CalS) genes in Arabidopsis (Arabidopsis thaliana), five are suggested or proven from mutational and correlative analyses to encode isoforms with important functions in pollen development (GSL1, GSL2, GSL5, GSL8, and GSL10; Enns et al, 2005;Nishikawa et al, 2005;Tö ller et al, 2008;Huang et al, 2009). Two genes have been implicated in cytokinesis, cell plate formation, and cell patterning (GSL6 and GSL8; Hong et al, 2001;Chen et al, 2009;Thiele et al, 2009) and one in response to attack by fungal pathogens (GSL5; Jacobs et al, 2003;Nishimura et al, 2003;Dong et al, 2008). Expression of the GSL6 gene is elevated and callose is deposited locally in response to phloem feeding by silverleaf whitefly nymphs (Bemisia sp.…”
mentioning
confidence: 99%